HUBUNGAN LAMA MENJALANI HEMODIALISA DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIS DI RSUP H. ADAM MALIK MEDAN - Sembiring, Friska Br; Pakpahan, Rotua Elvina; Tumanggor, Lili Suryani; Laiya, Epy Karniat Gustin (Universitas Murni Teguh, 2024)
Chronic kidney failure is a disease in which the function of the kidneys decreases so that they are unable to work in terms of filtering and disposing of the body's electrolytes.This condition causes patients with chronic kidney failure to undergo hemodialysis therapy which is carried out 2-3 times a week for a lifetime. This study aims to determine the relationship between the length of time undergoing hemodialysis and the quality of life of chronic kidney failure patients at H. Adam Malik General Hospital Medan 2023. This study uses a correlational design with a cross sectional approach. The population of this study are 376 people. The sampling technique used is purposive sampling, which total 79 samples. The instrument used is the Kidney Disease Quality of Life Questionnaire Short Form 36 (KDQOL-SF36). The results showed that most of the respondents underwent hemodialysis < 1 year as many as 36 people (45.6%), and most of them have a high quality of life as many as 46 people (58.2%). The results of statistical tests using the chi-square test obtained p-value = 0.103 (p> 0.05). Based on the result of the study, it can be concluded that there is no relationship between the length of time undergoing hemodialysis and quality of life of chronic kidney failure patients at H. Adam Malik General Hospital Medan in 2023. Suggestions from this study are that patients can carry out hemodialysis therapy regularly in order to achieve a good quality of life. Abstrak Gagal ginjal kronis adalah penyakit dimana fungsi organ ginjal mengalami penurunan hingga tidak mampu bekerja dalam hal penyaringan dan pembuangan elektrolit tubuh. Kondisi tersebut menyebabkan penderita gagal ginjal kronis harus menjalani terapi hemodialisa yang di lakukan 2-3 kali seminggu untuk seumur hidup. Penelitian ini bertujuan untuk mengetahui hubungan lama menjalani hemodialisa dengan kualitas hidup pasien gagal ginjal kronis di RSUP H. Adam Malik Medan Tahun 2023. Penelitian ini menggunakan rancangan penelitian korelasional dengan pendekatan cross sectional. Populasi dalam penelitian ini sebanyak 376 orang. Teknik pengambilan sampel yang di gunakan adalah Purposive sampling, yang berjumlah 79 sampel. Instrumen yang di gunakan adalah Kuesioner Kidney Disease Quality of Life Short Form 36 (KDQOL-SF36). Hasil penelitian menunjukkan bahwa sebagian besar responden menjalani hemodialisa < 1 tahun sebanyak 36 orang (45,6%), dan sebagian besar memiliki kualitas hidup tinggi sebanyak 46 orang (58,2%). Hasil uji statistik menggunakan chi-square test di peroleh p-value = 0,103 (p>0,05). Berdasarkan hasil penelitian dapat di simpulkan bahwa tidak ada hubungan lama menjalani hemodialisa dengan kualitas hidup pasien gagal ginjal kronis di RSUP H. Adam Malik Medan Tahun 2023. Saran dari penelitian ini diharapkan pasien dapat melaksanakan terapi hemodialisa secara teratur agar tercapai kualitas hidup yang baik.